A study of correlations between newborn children outcomes and emotional states and attachment to a fetus in women pregnant using in-vitro fertilization - Bokhan, Tatiana G.; Terekhina, Olga V.; Shabalovskaya, Marina V.; Silaeva, Anna V.; Leshchinskaia, Svetlana B.; Gayfulina, Zhanna Ph; Aparina, Kristina V.; Malykh, Sergey B.; Kovas, Yulia V. (Психология. Журнал Высшей школы экономики)
Children's development in the early years is significantly linked to further well-being. Among many factors involved in early development are mother’s attachment to the fetus and her emotional state during pregnancy. The current study prospectively explores mothers’ characteristics during the third trimester of pregnancy and their newborn children outcomes. The sample included 300 women with natural conception (NC) and 127 women with in-vitro fertilization (IVF), and their newborn children. For mothers, the following instruments were used: the Maternal Fetal Attachment Scale, the Clinical Scale for Self-assessment of Irritability, Depression and Anxiety. For newborns, the following parameters of newborn children outcomes were assessed: gestational period; the length and weight; the Apgar score in the first and fifth minutes after birth. All components of maternal attachment to the fetus were in the normal range for most women in both groups. All aspects of maternal attachment to the fetus were significantly greater in the IVF group. In both groups, more than 35% of women experienced depression and 43% of women experienced moderate/severe levels of anxiety. In the NC group, greater scores on giving of self and enjoying of watching tummy jiggle as the baby kicks inside were associated with less irritation in mothers. In the IVF group, the indicators of women’s attachment to their fetus were not associated with emotional states. Neither mothers’ attachment to their fetus nor their emotional states during pregnancy predicted newborn children outcomes. Children born from IVF had a statistically lower gestational period than in the NC group.